Implementing yoga within the school curriculum: a scientific rationale for improving social-emotional learning and positive student outcomes. Issue 1 (21st March 2016) - Butzer, Bethany; Bury, Denise; Telles, Shirley; Khalsa, Sat Bir S.
Abstract : Purpose: – The purpose of this paper is to review and synthesise research evidence and propose a theoretical model suggesting that school-based yoga programs may be an effective way to promote social-emotional learning (SEL) and positive student outcomes. Design/methodology/approach: – This paper is a literature review focusing on: the current state of research on school-based yoga interventions; a preliminary theoretical model outlining the potential mechanisms and effects of school-based yoga; similarities, differences and possibilities for integrating school-based SEL, yoga and meditation; practical implications for researching and implementing yoga in schools. Findings: – Research suggests that providing yoga within the school curriculum may be an effective way to help students develop self-regulation, mind-body awareness and physical fitness, which may, in turn, foster additional SEL competencies and positive student outcomes such as improved behaviours, mental state, health and performance. Research limitations/implications: – Given that research on school-based yoga is in its infancy, most existing studies are preliminary and are of low to moderate methodological quality. It will be important for future research to employ more rigorous study designs. Practical implications: – It is possible, pending additional high-quality research, that yoga could become a well-accepted component of school curricula. It will be particularly important for future research to examine possibilities around integrating school-based yoga and meditation with SEL programs at the individual, group and school-wide levels. Originality/value: – This paper is the first to describe a theoretical model specifically focused on school-based yoga interventions, as well as a discussion of the similarities and differences between school-based yoga, SEL and meditation.